IPVA e guerra fiscal: a competência dos Estados-membros e do Distrito Federal para instituição e cobrança do IPVA e os conflitos federativos - Carneiro, Luísa Cristina Miranda (2015)
This research s purpose is studying the limits of the taxing competence granted to the States and the Federal District to legislate and impose the Vehicle Property Tax (IPVA), from the analysis of the aspects of the Matrix-rule of tax levy, built on the basis of constitutional provisions and infra constitutional rules, and under the methodology of Constructivism Logical-Semantic. IPVA was created in 1985 and is considered a simple tax by the doctrine. However, it has become increasingly important in the Brazilian legal scenario, which is revealed by the increase of its revenues, the growth of various disputes towards the tax, and the notorious tax war between States, which compromises the integrity the federal pact, creates legal uncertainty and undermine both the States and the taxpayers that act in good faith